Climatological patterns of heatwaves during winter and spring 2023 and trends for the period 1979–2023 in central South America - Marengo, Jose A.; Costa, Mabel Calim; Cunha, Ana Paula; Espinoza, Jhan-Carlo; Jimenez, Juan C.; Libonati, Renata; Miranda, Vitor; Trigo, Isabel F.; Sierra, Juan Pablo; Geirinhas, Joao L.; Ramos, Andrea M.; Skansi, Milagros; et al. (Frontiers in Climate, 2025)
In the last 40 years, trends in heat wave frequency, intensity, and duration have increased steadily around the world. These intense heat waves were characterized persistent atmospheric blocking episode, with a continuous presence of a warm air mass and lack of rain for several consecutive days, that contributed to pronounced positive temperature anomalies, reinforced by extremely low soil moisture, and warm and drought conditions. The year 2023 was the warmest year on record, and the global average temperature was +1.45°C above pre-industrial (1850–1900) values worldwide. In South America 2023 was the warmest since 1900, with 0.81°C above the 1991–2020 reference period. Central South America experienced a sequence of heatwaves series being the most intense during the autumn and spring of 2023. From August to December 2023, the meteorological services of Brazil, Argentina, Paraguay and Bolivia reported record-high maximum temperatures in this period in several stations east of the Andes and identified 7 heat waves episodes that affected all these countries. The large-scale circulation patterns show that heatwaves were characterized by an anomalously high-pressure system that facilitated the formation of a heat dome through dry, hot air columns over a warm and dry soil. Several locations experienced temperature of about 10°C above normal, and some locations reported maximum temperatures above 40°C for several days in a row. These heat waves aggravated the drought over Amazonia during the second half of 2023, during an El Niño year. Compound drought-heat favored hydrological drought, while the increased dryness amplified the risk of fires.